Bound magneto-polaron in triangular quantum dot qubit under an electric field. (February 2016) - Fotue, A.J.; Issofa, N.; Tiotsop, M.; Kenfack, S.C.; Tabue Djemmo, M.P.; Wirngo, A.V.; Fotsin, H.; Fai, L.C.
Abstract: In this paper, we examine the time evolution of the quantum mechanical state of a magnetopolaron using the Pekar type variational method on the electric-LO-phonon strong coupling in a triangular quantum dot with Coulomb impurity. We obtain the Eigen energies and the Eigen functions of the ground state and the first excited state, respectively. This system in a quantum dot is treated as a two-level quantum system qubit and numerical calculations are done. The Shannon entropy and the expressions relating the period of oscillation and the electron-LO-phonon coupling strength, the Coulomb binding parameter and the polar angle are derived. Highlights: Evolution of the quantum state of magnetopolaron using Pekar type variational method on the electric-LO-phonon strong coupling. Triangular quantum dot with Coulomb impurity. The Eigen energies and the Eigen functions of the ground state and the first excited state. The Shannon entropy, Transition frequency and the period of oscillation for different control parameter.